New records of the genus Iotonchus (Mononchida, Iotonchidae) for Vietnam fauna and an updated key to species from Vietnam - Thanh Tam, Vu Thi (Academia Journal of Biology, 2015)
Five species of the genus Iotonchus (Cobb, 1916) Altherr, 1950, viz. Iotonchus arcuatus, I. candelabri, I. paracutus, I. pusillus and I. singaporensis, were recorded for the first time in Vietnam. All newly recorded species were also redescribed and illustrated, these species are recorded from Cat Ba and Bidoup-Nui Ba National Parks. In addition, the current status of two species, I. helicus and I. thui, which were originally discovered in Vietnam was discussed. An updated key to all extant species from Vietnam is also provided.